3D printing in the design of pharmaceutical dosage forms. (14th September 2019) - Souto, E. B.; Campos, J. C.; Filho, S. C.; Teixeira, M. C.; Martins-Gomes, C.; Zielinska, A.; Carbone, C.; Silva, A. M.
Abstract: Three-dimensional (3D) printing technologies are manufacturing approaches with widespread use in industry (e.g. automotive, automobile, pharmaceutical industries). With regard to its use in pharmaceutical industry, 3D printing is demonstrating to be of added value attributed to the possibility of printing tailored pharmaceutical products, namely personalized medical devices, such as implants and other dosage forms. However, with the approval of the first 3D-printed drug-product in 2015, a new perspective has arisen, i.e. the use of this technology to produce solid oral dosage forms exhibiting complex drug release profiles and allowing for individual dosing. Technological hurdles and regulatory issues still have to be overcome before this technology can truly find its place in the healthcare sector, where it can certainly contribute to a personalized and patient-centered healthcare. This manuscript offers a comprehensive analysis of the most extensively used methods of 3D printing in the pharmaceutical field, with examples of solid oral dosage forms and other medical devices currently under development or already marketed.